2008
DOI: 10.1016/j.clinph.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Seizure suppression by EEG-guided repetitive transcranial magnetic stimulation in the rat

Abstract: Objective-To test the anticonvulsive potential of a range of repetitive transcranial magnetic stimulation (rTMS) frequencies by novel methods for simultaneous EEG and rTMS in a rat seizure model. Methods-Seizureswere triggered by intraperitoneal kainic acid (KA; 10 mg/kg). Rats (n = 21) were divided into three groups in which individual seizures were treated with rTMS trains at one of three frequencies: 0.25, 0.5 or 0.75 Hz. EEG was continuously viewed by an operator who identified each seizure onset. Consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 33 publications
0
39
1
1
Order By: Relevance
“…При низкочастотной ритмиче-ской ТМС (рТМС) у крыс была показана связь эф-фекта долговременного торможения с работой глута-матергических рецепторов НМДА-типа [43]. Возможности ТМС-ЭЭГ пока еще не достаточно изучены на грызунах, хотя в отдельных работах метод уже использовали, например, для анализа противо-судорожного эффекта рТМС у крыс [44]. В перспек-тиве ТМС-ЭЭГ может стать мощным инструментом трансляционных исследований.…”
Section: том 7 Volunclassified
“…При низкочастотной ритмиче-ской ТМС (рТМС) у крыс была показана связь эф-фекта долговременного торможения с работой глута-матергических рецепторов НМДА-типа [43]. Возможности ТМС-ЭЭГ пока еще не достаточно изучены на грызунах, хотя в отдельных работах метод уже использовали, например, для анализа противо-судорожного эффекта рТМС у крыс [44]. В перспек-тиве ТМС-ЭЭГ может стать мощным инструментом трансляционных исследований.…”
Section: том 7 Volunclassified
“…(Godlevsky et al 2006) A more recent study suggests that TMS can suppress kainate-induced seizures in rats at frequencies of 0.5 and 0.75Hz though not at 0.25 Hz, demonstrating a frequency dependence on seizure control. (Rotenberg et al 2008) On the other hand, higher frequency stimulation has been shown to have confounding effects. Using male Wistar rats, it was shown that in the pentylenetrazole model of clonic seizures, chronic high-frequency stimulation (50Hz) may induce kindling of seizure activity, though this effect was not appreciated with acute-only stimulation.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…TMS-EEG also detects seizure improvement or exacerbation, making it a valuable clinical tool for everyday practice. TMS-EEG was recently applied in a small series of epilepsia partialis continua (EPC) to detect seizure suppression and to exclude seizure exacerbation during rTMS in animal models [144][145][146] and in humans [147][148][149][150]. Encouragingly, rTMS did not induce seizures, while seizure suppression was detected in some instances.…”
Section: Tms In Epilepsy: a Rationale For Neuromodulationmentioning
confidence: 99%